Goat's milk: characteristics and possibility - Ljubica Tratnik (Mljekarstvo, 2002)
Goat's milk today gets more and more attention. In comparison with other types of milk, the production of goat's milk increases the most. Although, the basic composition of goat's and cow's milk is very similar, goat's milk has an important dietetic and therapeutic advantages. In spite of that goat's milk is less explored. In this paper all main components of goat's milk and the somatic cells number are compared with cow's milk. Special emphasis is given on taste and therapeutic value of goat's milk and goat's milk products (cheeseand fermented milk).